Cerebral open flow microperfusion: A new in vivo technique for continuous measurement of substance transport across the intact blood–brain barrier. (December 2013) - Birngruber, Thomas; Ghosh, Arijit; Perez‐Yarza, Veronica; Kroath, Thomas; Ratzer, Maria; Pieber, Thomas R; Sinner, Frank
Summary The blood–brain barrier (BBB) limits substance transport to the brain and is therefore the major hurdle to overcome when developing neuroactive drugs. Herein, we report on cerebral open flow microperfusion (cOFM) as a new membrane‐free technique for measuring substance transport across the intact BBB. The cOFM technique is based on a probe that is inserted into the brain, rupturing the BBB. The BBB is re‐established within 15 days, which then allows sampling of interstitial brain fluid under physiological conditions. The aims of the present proof‐of‐concept study were to: (i) determine the time between cOFM probe insertion and BBB re‐establishment; and (ii) demonstrate the ability of cOFM to sample the interstitial cerebral fluid with an intact BBB. The cOFM probe was inserted into the frontal lobe of Sprague–Dawley rats, resulting in BBB rupture. Re‐establishment of the BBB was determined using Evans blue (EB) dye, which is an established marker for BBB intactness because it does not cross the intact BBB. Evaluating EB levels in the brain tissue indicated that the BBB was healed 11 days after probe insertion. To demonstrate transport across the healed BBB, we used sodium fluorescein (Naf), a sensitive, low molecular weight marker that can cross the intact BBB and can be used to monitor changes in BBB permeability. Significantly increased Naf levels were found in the interstitial fluid when hyperosmolar mannitol (known to open the BBB) was introduced via cOFM, which indicated partial opening of the BBB surrounding the cOFM probe. In conclusion, we show herein that cOFM allows monitoring of BBB permeability, which should be useful for measuring pharmacokinetics across the BBB and pharmacodynamics in the brain.